2017
DOI: 10.1098/rsob.170087
|View full text |Cite
|
Sign up to set email alerts
|

Role of long-chain acyl-CoAs in the regulation of mycolic acid biosynthesis in mycobacteria

Abstract: One of the dominant features of the biology of Mycobacterium tuberculosis, and other mycobacteria, is the mycobacterial cell envelope with its exceptional complex composition. Mycolic acids are major and very specific components of the cell envelope and play a key role in its architecture and impermeability. Biosynthesis of mycolic acid (MA) precursors requires two types of fatty acid synthases, FAS I and FAS II, which should work in concert in order to keep lipid homeostasis tightly regulated. Both FAS system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
(117 reference statements)
0
16
0
Order By: Relevance
“…The question remains how MadR is able to differentially bind to DNA in response to environmental changes. In mycobacteria, other TFs regulating mycolate biosynthesis are modulated by long‐chain acyl‐CoAs (Biswas et al , ; Mondino et al , ; Tsai et al , ), proposing a role for these molecules in the modulation of MadR as well. Similarly, a MadR homolog in Pseudomonas aeruginosa , DesT, was shown to have enhanced DNA binding in the presence of unsaturated acyl‐CoAs (Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The question remains how MadR is able to differentially bind to DNA in response to environmental changes. In mycobacteria, other TFs regulating mycolate biosynthesis are modulated by long‐chain acyl‐CoAs (Biswas et al , ; Mondino et al , ; Tsai et al , ), proposing a role for these molecules in the modulation of MadR as well. Similarly, a MadR homolog in Pseudomonas aeruginosa , DesT, was shown to have enhanced DNA binding in the presence of unsaturated acyl‐CoAs (Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The first transcriptional regulator of the main fasII operon ( fabD-acpM-kasA-kasB ) that was characterized is MabR [48]. Genetic studies showed that mabR is essential for M. smegmatis survival and biochemical analysis carried out in a mabR conditional mutant strain showed alterations in mycolic acid and in de novo FA biosynthesis, demonstrating for the first time the existence of a crosstalk between the two FAS systems and confirming MabR as one of the key modulator of lipid homeostasis in Mycobacterium [48,49]. A second non-essential transcription factor, FadR, that represses the fasII operon expression has also been described [50].…”
Section: Lipid Metabolism and Regulation Within The Hostmentioning
confidence: 99%
“…Analysis of a conditional mutant in M. smegmatis showed that FasR is a transcriptional activator and proved its essential role in mycobacteria viability. Interestingly, the activity of all these transcription factors (MabR, FadR and FasR) is modulated by long chain acyl-CoAs, the products of the FAS I system, highlighting a key role for these molecules in the modulation of lipid biosynthesis in mycobacteria [49,50,53]. An important difference between MabR and FasR with other bacteria transcriptional regulators of FA biosynthesis is that these two proteins are essential for bacterial survival while all the others are not.…”
Section: Lipid Metabolism and Regulation Within The Hostmentioning
confidence: 99%
“…MA synthesis is regulated at the fatty acid synthesis step. Fatty acid synthase genes are transcriptionally regulated in response to acyl‐CoA in C. glutamicum and mycobacteria (Nickel et al ., ; Salzman et al ., ; Mondino et al ., ; Irzik et al ., ; Tsai et al ., ). Moreover, FAS‐II components in M. tuberculosis are post‐translationally regulated by Ser/Thr protein kinase‐mediated phosphorylation (Molle et al ., ; Bhatt et al ., ; Slama et al ., ; Vilcheze et al ., ).…”
Section: Introductionmentioning
confidence: 97%